Estudo de rigidez de cadeias cinemáticas fechadas - Gonçalves, Rogério Sales (2009)
Multibody systems consist on a kinematic chain composed of links that can be rigid or flexible, interconnected by joints. The multibody systems are of great importance and are used in various applications such as in aerospace and automobile engineering, machine tools, mechanisms, sea exploration, medicine and robotics. An example of multibody system that has been widely studied in recent years is called parallel structure, which presents advantages over serial structures. In spite of its several advantages, this type of structure presents challenges to researchers on what concerns the solution of problems such as singularities, stiffness and accuracy. This thesis discuss the stiffness of complex kinematic chains directed to the parallel structures, due to their large industrial application, and the results can be applied to other closed kinematic chain systems, such as in vehicle structures. A review on the study of the stiffness of robotic structures was carried out in the literature, highlighting its advantages and disadvantages. It is also proposed the use of the stiffness method of analysis using the Matrix Structural Analysis theory (MSA) coupled to the kinematic model of the structure and main sources of flexibility of robotic structures: links and joints. This thesis is one of the pioneers to compare different methods of analysis of stiffness, showing its advantages and disadvantages. Numerical and experimental examples are presented applying the method MSA. It is also presented a new methodology for analyzing singularities through MSA method and conditional numbers. Finally, a new methodology was proposed for considering clearances in joints on multibody systems, with an application on a planar mechanism.